Visceral Adiposity Predicts Severity of Acute Pancreatitis. Issue 6 (July 2017) - Natu, Ashwinee; Stevens, Tyler; Kang, Lorna; Yasinow, Scott; Mansoor, Emad; Lopez, Rocio; Glessing, Brooke; Remer, Erick; Richards, Tyler; Gupta, Amit; Chak, Amitabh; Lee, Peter J.W.
Abstract : Objectives: The aim of this study was to determine the association of visceral adiposity with severe outcomes in acute pancreatitis (AP). Methods: This retrospective study included consecutive patients with AP admitted to a tertiary care hospital between January 2010 and January 2015 who underwent a computed tomography scan. The visceral adipose tissue (VAT) volume was estimated using the method of Linder and colleagues. Multivariable logistic regression analysis was conducted to assess VAT as a predictor of severe AP compared with other validated predictors of severity. Results: Five hundred and seventy four patients were admitted during the study period, of which 252 had a computed tomography scan available. Patients with severe AP had a larger VAT area compared with those with mild or moderate AP (mean: 184.9 cm 2 vs 79.9 cm 2, P = 0.006). Patients who developed multisystem organ failure or had acute necrotic collections had a larger VAT area than those who did not (150.6 cm 2 vs 91.0 cm 2, P = 0.004 and 174.0 cm 2 vs 91.9 cm 2, P = 0.003, respectively). Visceral adipose tissue area demonstrated superior discrimination of severe AP compared with other severity predictors. Conclusions: Increased VAT area is a strong predictor of severe pancreatitis, necrosis, and multisystem organ failure.